Islamic Judiciary in Human Rights: A Review from the Perspective of Maqasid al-Shariah - Muhajir M; Kurniati K; Zulhasari Z (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of Human Rights (HAM) in Indonesia from the perspective of Islamic justice through the lens of Maq??id al-Syar?'ah. Using a normative-empirical method, this research analyzes the gap between the normative aspects (the 1945 Constitution and Law No. 39/1999) and the empirical reality of human rights enforcement in the field. The findings indicate that, formally, Indonesia's human rights regulations are aligned with the principles of Maq??id al-Syar?'ah, particularly in protecting five essential aspects: religion, life, intellect, lineage, and property. However, implementation still faces structural, cultural, and political challenges, resulting in inequalities of justice, discrimination, and weak protection for vulnerable groups. The main opportunities lie in constitutional support and local values, while the solutions offered by Maq??id al-Syar?'ah include integrating the value of public interest (maslahah) into legal policies, human rights education for the public, law enforcement training, cross-cultural and interfaith dialogue, and strict sanctions for violators. This study concludes that systematic alignment between norms and practice through a maq??id approach is necessary for justice to be felt equally by all citizens.